2017
DOI: 10.1159/000485906
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Treatment Protects Mice Against Chronic Pancreatitis by Restoring Regulatory T Cells Loss

Abstract: Background/Aims: Chronic pancreatitis is an inflammatory disease of the pancreas characterized by progressive tissue destruction and fibrogenesis. The development of chronic pancreatitis is associated with immune cell dysregulation. Currently, the specific and effective treatment of chronic pancreatitis remains absent. Methods: By using an L-arginine induced chronic pancreatitis mouse model, we tested the therapeutic potential of hydrogen, a strong hydroxyl radicals scavenger, in the chronic pancreatitis model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…H 2 can also regulate inflammation by regulating the physiological pathway of T cells. For example, hydrogen treatment can inhibit the overactivation of the immune system by restoring the loss of regulatory T cells (Tregs) [ 15 ] and alleviates inflammation by preventing activation-regulated chemokine-mediated T-cell chemotaxis. The regulation effects of H 2 on programmed cell death, oxidative stress, and mitochondrial function are closely related to the inflammatory response.…”
Section: Mechanisms Of the Action Of Hmentioning
confidence: 99%
See 1 more Smart Citation
“…H 2 can also regulate inflammation by regulating the physiological pathway of T cells. For example, hydrogen treatment can inhibit the overactivation of the immune system by restoring the loss of regulatory T cells (Tregs) [ 15 ] and alleviates inflammation by preventing activation-regulated chemokine-mediated T-cell chemotaxis. The regulation effects of H 2 on programmed cell death, oxidative stress, and mitochondrial function are closely related to the inflammatory response.…”
Section: Mechanisms Of the Action Of Hmentioning
confidence: 99%
“…Recent studies have found that H 2 can relieve the dysregulated Th1/Th2 balance and can influence the number of T-regulatory cells (Tregs). H 2 was first reported to restore Treg loss in a rat model of chronic pancreatitis [ 15 ] and was later proven to increase CD4+CD25+Foxp3+Treg cells and significantly reduce nasal mucosa damage in animals with allergic rhinitis, which may be secondary to the restoration of Th1/Th2 balance [ 37 ]. Upregulation of Tregs has been reported in cerebral I/R models [ 28 ].…”
Section: Mechanisms Of the Action Of Hmentioning
confidence: 99%
“…In the L-arginine based CP model, Chen et al tested the therapeutic potential of hydrogen treatment as a potent scavenger of hydroxyl radicals. There was an overall improvement in CP pathology upon hydrogen treatment, as L-arginine-induced pancreatitis leads to ROS-mediated T-lymphocyte apoptosis, especially T-regs, and restoration of depleted T-regs by hydrogen treatment decreased disease severity and promoted their survival [39]. Apart from the pancreatitis-associated antigens and IL-10-producing FoxP3 + T-regs, CP patients have an increased number of antigen-specific CCR7 + CD45RA − central memory T-cells as compared to the healthy and CP-resected controls [40].…”
Section: Adaptive Immunity In Chronic Pancreatitismentioning
confidence: 98%
“…Using natural products, such as apigenin, rhein and tocotrienol-rich fraction (TRF) from palm oil, for targeting PSCs shows promise in reversing fibrosis in CP [100][101][102]. Some reports demonstrate that recovering T-reg loss and restoring IL-10 levels during CP suppress CD8 + T-cell over-activation and hence reduces the severity of CP [39,86]. Apart from targeting, the major area of focus in pancreatitis research at present is finding a robust, reliable and promising diagnostic marker for determining the severity of AP and MOF driven by AP.…”
Section: Impact Of Targeting the Adaptive Immune Arm In Pancreatitismentioning
confidence: 99%
“…However, the effective target and the precise molecular mechanisms of H 2 are not clear. Recent studies have indicated that H 2 can regulate both innate and adaptive immune responses, such as inhibiting lipopolysaccharide/interferon γ-induced NO via blocking ASK-1 and its downstream signaling molecules, p38 and JNK, as well as IκBα in macrophages [70], restoring the L-arginine-induced CD25 + Foxp3 + regulatory T cells loss in mice [71]. However, the functions of H 2 in regulating cardiovascular immune responses still need further investigation.…”
Section: Perspectivementioning
confidence: 99%